Super-homem moderno: análise da relação trabalha-saúde de gerentes de bancos públicos e privados - Máximo, Thaís Augusta Cunha de Oliveira (2009)
For a long time, studies related to managers had been limited, partly, due to the reputation of representatives and defenders of the corporation`s best interests, which they had for society. Recently, with productive restructuration, the management category, once preserved, reaches the position of victim of instability and of work intensification. This situation is particularly evident in managers that work with the financial sector, that due to its high competition, specific of this sector, are submitted to a constant dose of pressure for results. These considerations have motivated the present research, that has as its main goal to analyze the relationship between the work and health of managers from public and private banks, situated in the city of João Pessoa PB, and as specific goals to identify the procedures for insertion into workforce and professional graduation into management career; investigate the content and peculiarities specific of a management position; specify the conditions and work organization for bank managers; identify the sources of suffering/ pleasure at work, as well as the dynamics of notoriety; analyze the procedures adopted to mature the managers into the relationship between work and private life; describe the process health-disease in managers, in relation to their activity. The theoretical basis of this study gathers contributions from Ergology; Work Psychodynamics; Ergonomy of Activity and Clinics of Activity. As for the Method, with predilection to semi-structured interviews, focusing on the interest to access experiences, singularities and perspectives from bank managers in relation to their work. Sixteen main managers and intermediate managers from public and private banks in João Pessoa have collaborated to this research. Data analysis has been conducted throughout thematic content analysis. Considering what should be mentioned as Results, we identified that the goal management regulates the activity of managers daily and for some the deadlines can be suffocating. As sources of suffering, managers point out lack of appraisal from superiors and society; bad relationship with work colleagues/ team; discharges and consequences from Work Organization (labor hours, pressure for results, decisions without autonomy and system failures). As main sources of pleasure in management positions, they mentioned the appraisal from the work colleagues, clients and society; and the wages. In this panorama of difficulties, contradictions and surprises, the pairs show up as an important learning instrument and tutorship, with the exchange of their practical knowledge. About health, we identified that the main symptom related to management work would be Repetitive Strain Injury (RSI), Carpal Tunnel Syndrome, spinal cord stress, Gastrointestinal (GI) problems, (ulcers, gastritis, lack of appetite), high cholesterol, eyesight problems and dermatitis, and also psychic syndromes: anxiety, irritability, sleep changes (insomnia and nightmares with work), depression, tension, stress and lack of concentration. Another element raised up in this research was risk related to financial operations as well as the risk to personal security (kidnapping and robbery); what results in insecurity to managers and their families. We observed also that, in many cases, there`s a negative influence of work in family relationship, due to the fact that managers deal with a huge load of work and responsibility, which always brings them back home tired and preoccupied. Nonetheless, the feeling of having to be available anytime results in leaving the family as second best.